Conceptualising Austerity in Scotland as a Risk Shift: Ideas and Implications. Issue 4 (November 2016) - McKendrick, John H.; Asenova, Darinka; MacRae, Claire; Reynolds, Rebecca; Egan, James; Hastings, Annette; Mooney, Gerry; Sinclair, Stephen
Abstract : There is growing recognition that UK austerity measures impact adversely and more acutely on the most disadvantaged individuals, communities and groups. These changes may be understood as representing a shift of responsibility away from collectives to individuals. This paper explores these issues through the lens of risk analysis. Drawing on case study research from one neighbourhood in one Scottish local authority, it considers how the distinctive polity in Scotland, in the context of austerity, is redistributing social risk to vulnerable communities, groups and individuals. The local community is adapting, with varying degrees of success, to the risk transfers they are experiencing. Formal and informal risk mitigation measures are ameliorating, but not countering, these risks. The penultimate section of the paper is a collaborative endeavour. Drawing from a seminar discussion with key informants from academia, the Third Sector and government in Scotland, some of the implications of this 'risk shift' are discussed; particularly in relation to extending personalisation, stresses on social capital, changing understanding of securities, demographic developments, widening social divisions and alternatives to austerity economics.